The 10-year Trend of TB Rate in West Azerbaijan Province, Iran from 2001 to 2010. - Abbas Rahimi Foroushani; Fereshteh Farzianpour; Afshin Tavana; Javad Rasouli; Shayan Hosseini (Tehran University of Medical Sciences, 2014)
The present study aimed to explore some risk factors affected the mean of the number of tuberculosis (TB) in West Azerbaijan Province, Iran between 2001 and 2010.Our time series study analyzed the data of 2,560 TB patients as registered with TB Patients Care System in West Azerbaijan Province from early 2001 to 2010. A checklist was prepared for collecting the data and they were then analyzed in SPSS V.16 software.The percentage of male and percentage of female were close to each other (52.2% against 47.8%, respectively). A significant increasing trend of TB rate was found over the years of 2001and 2010 with a pick at 2008 (P